Design and manufacture of a soft tourniquet for regulation of arterial oclussion pressure (2024)
In the search for better ways to improve medical care during emergencies, it is crucial to develop better technologies that can handle bleeding and other related complications that may arise from injuries. The motivation of this project is to design and manufacture a tourniquet based on the soft robotics technology with the main objective of controlling the blood pressure of patients reducing tissue damage. This work will describe the research, design and manufacture of various models, simulation, experimental testing and future work of a Soft Tourniquet.